2017
DOI: 10.1097/mao.0000000000001267
|View full text |Cite
|
Sign up to set email alerts
|

Can the Risks of Cerebrospinal Fluid Leak After Vestibular Schwannoma Surgery Be Predicted?

Abstract: The predictors of CSF leak after TLA for vestibular schwannoma are young age, male sex, longer duration of surgery, which adjusting for BMI. In this regard, the surgical team should adapt its management during pre- and postoperative period to decrease the likelihood of a leak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 15 publications
1
41
0
Order By: Relevance
“…Reported rates of CSF leak following VS resection in the literature are quite variable: studies reported 2.4 to 12.0% in recent literature. 2,[4][5][6][8][9][10] The rate of CSF leak was observed to be significantly higher in TL approaches for VS. 4,5 While we observed a difference in CSF leak rates between TL group and no TL group (►Table 2), that difference was not statistically significant on multivariate regression analysis controlling for age, gender, and operative time. As mentioned in our results, the operative times were longer on average for the TL group and that may have accounted for the higher risk of CSF leaks in our data.…”
Section: Csf Leakmentioning
confidence: 95%
See 4 more Smart Citations
“…Reported rates of CSF leak following VS resection in the literature are quite variable: studies reported 2.4 to 12.0% in recent literature. 2,[4][5][6][8][9][10] The rate of CSF leak was observed to be significantly higher in TL approaches for VS. 4,5 While we observed a difference in CSF leak rates between TL group and no TL group (►Table 2), that difference was not statistically significant on multivariate regression analysis controlling for age, gender, and operative time. As mentioned in our results, the operative times were longer on average for the TL group and that may have accounted for the higher risk of CSF leaks in our data.…”
Section: Csf Leakmentioning
confidence: 95%
“…Russel et al identified males and younger patients as demographics at greater risk in a TL approach cohort. 5 He found that surgical times had a more significant impact on CSF leaks (OR: 1.85). Our findings corroborate prior findings that prolonged surgical time increases the likelihood of CSF leak.…”
Section: Csf Leakmentioning
confidence: 98%
See 3 more Smart Citations